Nonalcoholic Fatty Liver Disease (NAFLD)—A New Cardiovascular Risk Factor in Peritoneal Dialysis Patients. Issue 4 (July 2016) - Mikolasevic, Ivana; Milic, Sandra; Racki, Sanjin; Zaputovic, Luka; Stimac, Davor; Radic, Mladen; Markic, Dean; Orlic, Lidija
Background: Recent investigations indicated that nonalcoholic fatty liver disease (NAFLD), a hepatic component of metabolic syndrome (MS), is associated with an increased risk of cardiovascular disease (CVD). Accordingly, we were interested in exploring the frequency of NAFLD in peritoneal dialysis (PD) patients and analyzing factors in PD patients associated with NAFLD occurrence. In addition, we were interested in investigating whether NAFLD is associated with higher CVD risk in our PD patients. Methods: In the present cross-sectional study, we analyzed 58 PD patients. The controlled attenuation parameter (CAP) was used to detect and quantify liver steatosis with the help of transient elastography (TE) (FibroScan, Echosense SA, Paris, France). A carotid ultrasound was performed in all patients to measure carotid intimae media thickness (IMT) and plaque as surrogate measures of increased CVD risk, and we investigated their association with NAFLD. Results: Nonalcoholic fatty liver disease was present in 74.1% of PD patients. Peritoneal dialysis/nonalcoholic fatty liver disease patients had statistically greater daily (136.5 ± 62.6 vs 93.6 ± 36.1; p = 0.02) and monthly (4, 095.3 ± 1, 877.7 vs 2, 806.6 ± 1, 083.2; p = 0.02) glucose load in comparison to the non-NAFLD/PD patients. In the next step, we were interested in analyzing what demographic and clinical characteristics in our PD patients are associated with a higher NAFLD occurrence. Presence of diabetes mellitus (DM), arterial hypertension (AH), dyslipidemia, body mass index > 25 kg/m 2, and daily glucose load > 100 g were associated with NAFLD occurrence. Peritoneal dialysis patients with NAFLD showed more carotid atherosclerosis than PD patients without NAFLD. In addition, CAP values (as indicator of liver steatosis) showed strong positive association with IMT (r = 0.801; p < 0.0001). Nonalcoholic fatty liver disease was a strong predictor of carotid atherosclerosis in PD patients. Conclusion: Nonalcoholic fatty liver disease is highly prevalent in PD patients. Peritoneal dialysis patients with NAFLD are at high risk of atherosclerosis. Assessment of NAFLD in PD patients may be helpful for CVD risk stratification.